Effect of sex class on the levels of some biochemical variables in thalassemia patients - Khalaf N. Mohammed; Mossa M. Marbut (Tikrit Journal of Pure Science)
The study was conducted at Azadi Teaching Hospital - Thalassemia Center for the period from 1/10/2017 to 1/4/2018. It included 60 patients including 30 males and 30 females, as well as control group which included 20 Healthy people were all 10 to 21 years of age. The following variables were studied: ferritin, GSH, insulin-like growth factor-1 (IGF-1) Malondialdehyde (MDA) Interleukin-6 (IL-6), and Cortisol. The analysis of correlation coefficients and simple linear regression was carried out to determine the effect of the variables among them. The results were as follows: Thalassemia patients recorded the lowest levels of GSH, IGF-1 and cortisol at 2.2 μmol / L and 50.4 ng / ml and 10.11 μg / dL respectively, while the same group recorded the highest levels of ferritin, MDA and IL- 6 was 3083 ng / ml, 941 mmol / L and 368 pg / mol. There were significant effects of both sexes in the group of thalassemia patients in both ferritin, GSH, IGF-1, MDA, and IL-6 with 2573, 3592 μg / dL, 2.821, 1.573 μmol / L, 63.3, 37.47 ng / ml and 1163.1 719.3 mmol / L 300.9 and 435.6 pg / mol for males and females, respectively. The results of the correlation coefficient analysis showed existence of and low correlations in the negative and positive direction between the study variables of the two groups of patients and control. The results of the simple linear regression analysis showed positive and negative regression ratios of IL-6 and IGF-1 growth factor on the rest of the study variables.